Open Targets: a platform for therapeutic target identification and validation. Issue Volume 45:Issue D1(2017) (8th December 2016) - Koscielny, Gautier; An, Peter; Carvalho-Silva, Denise; Cham, Jennifer A.; Fumis, Luca; Gasparyan, Rippa; Hasan, Samiul; Karamanis, Nikiforos; Maguire, Michael; Papa, Eliseo; Pierleoni, Andrea; Pignatelli, Miguel; et al.
Abstract: We have designed and developed a data integration and visualization platform that provides evidence about the association of known and potential drug targets with diseases. The platform is designed to support identification and prioritization of biological targets for follow-up. Each drug target is linked to a disease using integrated genome-wide data from a broad range of data sources. The platform provides either a target-centric workflow to identify diseases that may be associated with a specific target, or a disease-centric workflow to identify targets that may be associated with a specific disease. Users can easily transition between these target- and disease-centric workflows. The Open Targets Validation Platform is accessible at https://www.targetvalidation.org .